Interaction between goniothalamin and peroxisomal multifunctional enzyme type 2 triggering endoplasmic reticulum stress. Issue 10 (October 2020) - Sophonnithiprasert, Thanet; Aruksakunwong, Ornjira; Tashiro, Etsu; Kondoh, Yasumitsu; Muroi, Makoto; Osada, Hiroyuki; Imoto, Masaya; Watanapokasin, Ramida
Abstract: Endoplasmic reticulum stress is one of the pathways involved in cell cytotoxicity. In this study, goniothalamin, one of styryllactone compounds found in plant Goniothalamus spp ., was observed to trigger ER stress in HeLa cell line. In addition, we demonstrated that peroxisomal multifunctional enzyme type2 (MFE2) was a specific goniothalamin-binding protein using an in vitro goniothalamin-linked bead pull-down assay. Since MFE2 has been reported to be an important mediator enzyme for peroxisomal β-oxidation of a very long chain fatty acid metabolism, therefore computational molecular docking analysis was performed to confirm the binding of goniothalamin and MFE2. The results indicated that goniothalamin structure binds to scp-2 domain, enoyl-CoA hydratase 2 domain and (3R)-hydroxyacyl-CoA dehydrogenase domain of MFE2. To further determine the effect of MFE2 on ER stress induction, MFE2 knockdown by siRNA in HeLa cell was conducted. The results implied that MFE2 triggered CHOP, a key mediator of ER stress-induced apoptosis, expression. Therefore, these data inferred that goniothalamin may interrupt the MFE2 function resulting in lipid metabolism perturbation associated with ER stress-independent activation of unfolded protein response. This is the first report to show that goniothalamin binds directly to MFE2 triggering ER stress activation probably through the lipid metabolism perturbation. Abstract : Cell biology; Bioinformatics; Biochemistry; Molecular biology; Goniothalamin, Peroxisomal multifunctional enzyme type 2 (MFE2), Endoplasmic reticulum stress, Computational molecular docking.